Lifestyle factors and breast cancer in a Moroccan population case-control study of the center Mohammed VI for cancer treatment - Houda, Drissi; Ezzahra, Imad Fatima; Karima, Bendahhou; Abdelatif, Benider; Driss, Radallah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The study aims to examine the association between lifestyle habits and breast cancer risk in a Moroccan population. Methods: This is a case-control study conducted at the Mohammed VI Centre for cancer treatment in Casablanca. Results: The results highlighted that family history of breast cancer (OR=5.73) and alcohol consumption (OR=3.76) were positively associated with breast cancer. Analysis of anthropometric parameters showed that the risk of developing breast cancer is estimated at 1.78 in overweight women and 2.39 in obese women compared to those of normal weight. The risk of developing breast cancer is estimated at 1.82 for women with a WC greater than 88 cm and 1.70 for women with a WHR greater than 0.85. At age 10, the risk is 1.60 for women with a large figure compared to women with a small figure. However, at age 40, the average body shape relative to the lean body was associated with a decreased risk of breast cancer. In addition, the data confirmed that physical activity participation decreases with age; in childhood and adolescence, women are more active while in post-menopause, women become moderately active. Being very active in childhood, peri-menopause and post-menopause seems to be a protective factor against the occurrence of breast cancer. Conclusions: The study showed that the risk of breast cancer is potentially high in elderly women, overweight women and women with a family history of cancer. This risk was increased by behavioral factors such as toxic habits and physical inactivity.